A Home-Based, Music-Cued Movement Program Is Feasible and May Improve Gait in Progressive Supranuclear Palsy - Wittwer, Joanne E.; Winbolt, Margaret; Morris, Meg E. (Frontiers in Neurology, 2019)
Objectives: To understand the benefits and feasibility of using supervised, home-based, music-cued training to improve gait speed and stability in community-dwelling people with Progressive Supranuclear Palsy. Design: Feasibility trial incorporating a single group repeated-measures design. Setting: Human movement laboratory and participants’ homes. Interventions: Two training sessions per week, conducted by experienced physiotherapists over four weeks. Each home training session consisted of a range of activities in standing or walking, with and without auditory cues. Rhythmic auditory cues were played via a portable digital music player and consisted of metronome beats and individually chosen, commercially available rhythmic music tracks. Main Outcome Measures: Spatiotemporal gait measures were recorded using an 8m long GAITRite® mat. Participants walked without cues at self-selected comfortable pace. The Progressive Supranuclear Palsy and Unified Parkinson’s Disease Rating Scales were administered at baseline. Addenbrooke’s Cognitive Examination-III, Geriatric Depression Scale, Assessment of Personal Music Preference Scale and Physiological Profile Assessment were administered at baseline and retest. Results: At baseline, two of the five community-dwelling people with Progressive Supranuclear Palsy who participated walked with normal speed and low gait variability. Of the remainder who walked with slower, more variable patterns, two walked faster at retest, one by a clinically meaningful amount. Four participants reduced timing variability at retest and three reduced step length variability. All participants reported high satisfaction levels with the program. Conclusions: When delivered at home with the support of carers, music-cued gait training can provide a feasible approach to improving disorders of gait stability in people with this rare, degenerative condition. Movement to music is engaging which can facilitate adherence to therapy.